(untitled) (Architecture Image Studies, 2025)
Indonesia is one of the world’s largest rattan producers. Cirebon is the central hub of the rattan furniture industry, contributing significantly to the local economy through craft production and exports. However, this industry generates a significant amount of waste, including rattan cuttings, shavings, and sawdust, most of which has not been optimally utilized despite the high potential of rattan waste. This study aims to analyze the types, characteristics, and potential value of rattan industry waste in Cirebon, using a qualitative descriptive method supported by field observations, in-depth interviews with stakeholders, and literature review. The research applied a SWOT analysis approach which describes strengths, weaknesses, opportunities, and threats to identify potentials to turn waste into resources, reduce environmental impacts, and create added value for local communities then the circular design approach was implemented to develop sustainable design concepts for rattan waste-based products as creative problem-solving can become an effective way to support this. This research shows that waste is a valuable resource that can be reintegrated as another useful product. This research provides fundamental insights that efficient waste classification can optimize material recycling and encourage product design innovation for sustainable product development in the industry. It supports the transition of the Cirebon rattan industry towards a more sustainable future. Further research is needed to examine adaptive manufacturing processes and the marketability of products made from rattan waste, to improve the implementation of circular design strategies in this sector.